2013
DOI: 10.1371/journal.pone.0054592
|View full text |Cite
|
Sign up to set email alerts
|

Human Chorionic Gonadotropin β Induces Migration and Invasion via Activating ERK1/2 and MMP-2 in Human Prostate Cancer DU145 Cells

Abstract: We previously demonstrated that human chorionic gonadotropin β (hCGβ) induced migration and invasion in human prostate cancer cells. However, the involved molecular mechanisms are unclear. Here, we established a stable prostate cancer cell line overexpressing hCGβ and tested hCGβ-triggered signaling pathways causing cell migration and invasion. ELISA showed that the hCGβ amount secreted into medium increased with culture time after the hCGβ-transfected cells were incubated for 3, 6, 9, 12 and 24 h. More, hCGβ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 30 publications
(31 reference statements)
6
21
0
3
Order By: Relevance
“…The results of this study are consistent with our proposed theory: by examining the distribution of the β-HCG positive cells, we found that β-HCG protein was mostly located at the invasive front of CRC tumors, the more malignant and aggressive tumor area in which the tumor cells are highly correlated with EMT [26]; while β-HCG had no influence on tumor proliferation, it did promote CRC cell migration and invasion. In addition, Li et al reported that β-HCG promoted migration and invasion in prostate cancer by inhibiting E-cadherin and activating the ERK signaling pathway [27]. Our study also validated β-HCG did decrease the expression of E-cadherin, ZO-1 in membrane and enhance the β-catenin translocation from the membrane to nucleus.…”
Section: Discussionsupporting
confidence: 82%
“…The results of this study are consistent with our proposed theory: by examining the distribution of the β-HCG positive cells, we found that β-HCG protein was mostly located at the invasive front of CRC tumors, the more malignant and aggressive tumor area in which the tumor cells are highly correlated with EMT [26]; while β-HCG had no influence on tumor proliferation, it did promote CRC cell migration and invasion. In addition, Li et al reported that β-HCG promoted migration and invasion in prostate cancer by inhibiting E-cadherin and activating the ERK signaling pathway [27]. Our study also validated β-HCG did decrease the expression of E-cadherin, ZO-1 in membrane and enhance the β-catenin translocation from the membrane to nucleus.…”
Section: Discussionsupporting
confidence: 82%
“…MMP-2 is one of the most distinctive members of this family and facilitates prostate cancer cell invasion. Previous studies have demonstrated that MMP-2 expression is mediated by ERK1/2 (26,27,47,52). In the present study, we found that SFN significantly decreased MMP-2 expression and activity.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, sustained (>15 min stimulation) activation of ERK1/2 exhibited the opposite effects (17,(21)(22)(23)(24)(25). Previous results demonstrated that human chorionic gonadotropin β (hCGβ) promoted cell migration and invasion in human glioblastoma and prostate cancer cells by increasing the expression and activity of MMP-2, resulting from the sustained activation of ERK1/2 (26,27). It was also found that the sustained phosphorylation of ERK1/2 by SFN contributed to the suppression of migration and invasion in human glioblastoma cells (16).…”
Section: Introductionmentioning
confidence: 99%
“…The b-subunit of chorionic gonadotropin (CGb) is a quintessential product of trophoblast that is expressed by many trophoblastic and non-trophoblastic tumours [14,28] and has been considered a 'definitive cancer biomarker' [16]. Although CGb possesses anti-apoptotic and invasionpromoting activities [29,30], any role in cancer progression must be primate-specific because the duplications that generated a cluster of CGB genes from an ancestral LHB gene are primate-specific [31]. Many similar examples could be given.…”
Section: Trophoblast and The Subversion Of Extrinsic Defencesmentioning
confidence: 99%